RETRACTED: Developing ideal mission statements: lessons learned from top global organizations - Aftab Faisal; AboAlsamh Hoda Mahmoud; Ahmad Shabir; Siddiqui Kamran Ahmed (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001